Social change and African traditional religion - Pobee, John S.; Mends, Emmanuel H. (SA. Sociological Analysis, 1977)
Islam, christianity, nationalism and secularism are analyzed in their influences on African traditional religions. The peculiar mixtures and combinations of traditional and nontraditional elements are noted in various rites of passage, ceremonies and celebrations; and the often uneasy co-existence of these elements is analyzed.
free
Keywords: Africa – Religion; Africa – Social life and customs; Africa.; Islam; Social change